2020
DOI: 10.3390/biom10030364
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Mediates Melatonin’s Effects on Microglial Activation in Hypoxia: In Vitro and In Vivo Evidence

Abstract: Melatonin exerts direct neuroprotection against cerebral hypoxic damage, but the mechanisms of its action on microglia have been less characterized. Using both in vitro and in vivo models of hypoxia, we here focused on the role played by silent mating type information regulation 2 homolog 1 (SIRT1) in melatonin’s effects on microglia. Viability of rat primary microglia or microglial BV2 cells and SH-SY5Y neurons was significantly reduced after chemical hypoxia with CoCl2 (250 μM for 24 h). Melatonin (1 μM) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…Mechanistically, this may be achieved when melatonin directly or indirectly (most likely via inhibition of HIF1α) downregulates the enzyme pyruvate dehydrogenase kinase (PDK) which normally markedly inhibits the pyruvate dehydrogenase complex (PDC). 8 In other experimental models, melatonin has been shown to inhibit HIF1α 13 ; this suggestion is also consistent with the means by which other socalled glycolytics, for example, dichloroacetate, inhibit the Warburg effect. 14 PDC activity is essential for the intra-mitochondrial conversion of pyruvate, a glucose metabolite, to acetyl-coenzyme A ( Figure 1); this causes the cells to metabolize pyruvate in the cytosol with the development of aerobic glycolysis and associated metabolic changes including the marked upregulation of the pentose phosphate pathway for nucleotide synthesis and elevated production of other biomolecules (Figure 1).…”
Section: Commentarysupporting
confidence: 72%
“…Mechanistically, this may be achieved when melatonin directly or indirectly (most likely via inhibition of HIF1α) downregulates the enzyme pyruvate dehydrogenase kinase (PDK) which normally markedly inhibits the pyruvate dehydrogenase complex (PDC). 8 In other experimental models, melatonin has been shown to inhibit HIF1α 13 ; this suggestion is also consistent with the means by which other socalled glycolytics, for example, dichloroacetate, inhibit the Warburg effect. 14 PDC activity is essential for the intra-mitochondrial conversion of pyruvate, a glucose metabolite, to acetyl-coenzyme A ( Figure 1); this causes the cells to metabolize pyruvate in the cytosol with the development of aerobic glycolysis and associated metabolic changes including the marked upregulation of the pentose phosphate pathway for nucleotide synthesis and elevated production of other biomolecules (Figure 1).…”
Section: Commentarysupporting
confidence: 72%
“…However, melatonin effects were abolished by luzindole treatment. Previously, Sirt1 dependent Nrf2 expression has been reported, and after inhibition of Sirt1 via inhibitor, enhanced pro-inflammatory cytokines and as well as p-NF-κB expression were detected upon LPS administration, suggesting a sirt1 role in LPS induced neuroinflammation (Mendez-David et al, 2015;Santofimia-Castaño et al, 2015;Song et al, 2017;Shah et al, 2017;Ma et al, 2018;Wang et al, 2019;Merlo et al, 2020;Yi et al, 2020;Zhi W. et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Another study demonstrated that melatonin could alleviate microglial damage by sirtuin 1 (SIRT1) elevation in rats after common carotid artery ligation [35]. In vitro studies showed that melatonin protected and preserved the neuronal cell's function in the context of hypoxia and low glucose [13,35]. The application of melatonin also preserves the integrity of the blood-brain barrier after transient focal cerebral ischemia due to the inhibition of matrix metalloproteinase 9 (MMP9) [36,37].…”
Section: Melatonin and Cas-related Ischemic Strokementioning
confidence: 99%
“…The study also demonstrated that melatonin administration can significantly reduce infarcted area in the brain both in wild type and TLR4 −/− mice. Another study demonstrated that melatonin could alleviate microglial damage by sirtuin 1 (SIRT1) elevation in rats after common carotid artery ligation [35]. In vitro studies showed that melatonin protected and preserved the neuronal cell's function in the context of hypoxia and low glucose [13,35].…”
Section: Melatonin and Cas-related Ischemic Strokementioning
confidence: 99%